Court Considerations in the Termination of Parental Rights: A Comprehensive Analysis of Israeli Court Decisions. (October 2016) - Ben‐David, Vered
Abstract : Court decisions to terminate parental rights (TPR) have a major impact on parents and children, but the decision‐making process is unclear. Analysis of 261 Israeli TPR court cases indicated the dominance of considerations relating to normative parental functioning, the parents' ability to change, the impact of separating a child from his family, the parents' social normativity and educational ability. The legal considerations relate to the importance of the biological family, the necessity of adoption and the importance of a fair legal process. Insufficient consideration is accorded to cultural differences in parenting practices and the voice of the child. Key Points for the Family Court Community: This study analyzes key considerations of the courts in termination of parental rights cases. Judgments of parental capacity reflected implicitly or explicitly value or criteria on desirable parenting. Professional considerations deriving primarily from psychology and social work disciplines governed the legal discussion of parents and children's rights. Special weight has been accorded to the parents' social normativity. Insufficient consideration has been given to the social‐cultural context of parenting as well as to the loss of the child following his/her detachment from primary caregivers.